2020
DOI: 10.1371/journal.ppat.1008803
|View full text |Cite
|
Sign up to set email alerts
|

Closely related reovirus lab strains induce opposite expression of RIG-I/IFN-dependent versus -independent host genes, via mechanisms of slow replication versus polymorphisms in dsRNA binding σ3 respectively

Abstract: The Dearing isolate of Mammalian orthoreovirus (T3D) is a prominent model of virus-host relationships and a candidate oncolytic virotherapy. Closely related laboratory strains of T3D, originating from the same ancestral T3D isolate, were recently found to exhibit significantly different oncolytic properties. Specifically, the T3D PL strain had faster replication kinetics in a panel of cancer cells and improved tumor regression in an in vivo melanoma model, relative to T3D TD. In this study, we discover that T3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 81 publications
1
14
0
Order By: Relevance
“…Closely related reovirus strains are known to display differences in a variety of phenotypes (29)(30)(31). In previous work we showed that in cells infected with reovirus strain T3A, TNFα fails to induce the expression of NF-κB target genes due to loss of IKKβ and NEMO (13).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Closely related reovirus strains are known to display differences in a variety of phenotypes (29)(30)(31). In previous work we showed that in cells infected with reovirus strain T3A, TNFα fails to induce the expression of NF-κB target genes due to loss of IKKβ and NEMO (13).…”
Section: Resultsmentioning
confidence: 93%
“…We also demonstrate that in reovirus infected cells, properties of de novo synthesized σ3 impact the expression of NF-κB target genes. Curiously, polymorphic differences in σ3 between T3D L and T3D F (respectively referred to as T3D-PL and T3D-TD in these studies) have recently been demonstrated to regulate host gene expression (30). T3D L σ3 contributes to the greater capacity of T3D L to express RIG-I-and IFNindependent genes in comparison to T3D F .…”
Section: Discussionmentioning
confidence: 91%
“…Although there is no evidence showing reovirus dsRNA outside of VFs, the dsRNA in rotavirus-infected cells was detected in the cytoplasm outside of viroplasms, the site of rotavirus replication and assembly [ 105 ]. Multiple studies have shown that reovirus infection induces type I and type III IFN production and the up-regulation of multiple IFN-stimulated genes [ 106 , 107 , 108 ]. Viral genome dsRNA or dsRNA formed by secondary structures within viral mRNAs can stimulate a cascade of antiviral events.…”
Section: Role Of Pkr and Rnase L In Translation Suppressionmentioning
confidence: 99%
“…It is important to note differences between the two studies that may explain the differing results. Firstly, the oncolytic strain of T3D is genetically different to the T3D strain used by many labs and importantly has nonsynonomous changes within the S4 gene segment that affect replication and induction of the type I interferon response [ 108 , 123 ]. In addition, the study investigating reovirus-induced host shutoff infected cells at a high multiplicity of infection (80 PFU per cell) [ 114 ], whereas the study using the oncolytic strain of T3D used a lower multiplicity (10 PFU per cell) that does not induce host shutoff [ 122 ].…”
Section: Role Of Pkr and Rnase L In Translation Suppressionmentioning
confidence: 99%
“…For instance, given recent discoveries that the reovirus-translating ribosomes segregate in virus factories, did the methods by Skup, Zarbl and Millward also capture these species? Furthermore, given the recognition that reoviruses vary genetically and phenotypically from each other, even among different laboratory strains of serotype 3 Dearing (T3D) MRV, it would be interesting to determine whether uncapped RNAs are common to a broader collection of reovirus isolates [ 41 , 42 , 43 ]. Similarly, is this a unique characteristic of L929 cells or can it be observed in other cell types permissive to reovirus infection?…”
Section: Capping Status Of Viral Rnasmentioning
confidence: 99%